2004
DOI: 10.1258/0969141041732184
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis on the validity of pepsinogen test for gastric carcinoma, dysplasia or chronic atrophic gastritis screening

Abstract: Aim:To assess the validity of the measurement of pepsinogen I and II as a screening test for gastric cancer and pre-malignant lesions, namely low-grade dysplasia, both in the general population and in selected groups of patients. Methods:A meta-analysis of sensitivity and specificity results from individual papers on the use of the pepsinogen test. An intrinsic cut-off effect was assumed and a random effect model was used for pooling.Results: Forty-two data sets were included: 27 (64%) population-based screeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
154
3
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(167 citation statements)
references
References 48 publications
8
154
3
2
Order By: Relevance
“…[41][42][43] We utilized the validated cutoff levels employed routinely in Japan, namely, a PG I level of < 70 ng/ml and a PG I:II ratio of < 3.0. [44][45][46] Thus, we feel confident that the designation of atrophy was accurate and reflected the important histologic entity of corpus atrophy. In summary, we have found that a polymorphism in the PTPN11 gene that encodes SHP-2 increases the risk of gastric atrophy in H. pylori-positive patients.…”
Section: Discussionmentioning
confidence: 87%
“…[41][42][43] We utilized the validated cutoff levels employed routinely in Japan, namely, a PG I level of < 70 ng/ml and a PG I:II ratio of < 3.0. [44][45][46] Thus, we feel confident that the designation of atrophy was accurate and reflected the important histologic entity of corpus atrophy. In summary, we have found that a polymorphism in the PTPN11 gene that encodes SHP-2 increases the risk of gastric atrophy in H. pylori-positive patients.…”
Section: Discussionmentioning
confidence: 87%
“…However, the limited knowledge about their characteristics in different populations and the significant differences in methodologies may prejudice the assessment of consistency. For instance, different cut-off values are used for the positive definition when either PGⅠ levels or both PGⅠand PGⅡ levels are considered [11][12][13] . Furthermore, due to few cohort studies have been done in Chinese, the population-based data on serum PG levels and their influencing factors, such as age, sex, the presence of different gastric diseases and H pylori infection, are limited [14,15] .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, early identification and endoscopy of subjects with AG may facilitate the diagnosis of gastric cancer at an early stage, and may enable treatment of premalignant gastric lesions (intramucosal neoplasias) in an asymptomatic phase [6][7][8][9]. A low serum level of pepsinogen I (SPGI) is a reliable biomarker of AG and is, therefore, a tool to noninvasively delineate subjects with advanced AG who need a prompt diagnostic upper GI endoscopy because of increased cancer risk [1][2][3][4]. Correspondingly, it is conceivable that an early diagnosis of AG with a biomarker test followed with a diagnostic upper GI endoscopy will improve the cancer survival, resulting also in decrease of premature mortality.…”
Section: Discussionmentioning
confidence: 99%
“…It was known that SPGI levels of 25 microg/l or less indicate advanced (moderate or severe) atrophic gastritis (AG) in the gastric corpus and fundus with high reliability [1][2][3][4]. However, the indicators of structure, process, and outcome related to screening were completely unknown.…”
Section: Introductionmentioning
confidence: 99%